DERIVATIONAL SUFFIXES FORMING NOUN IN THE INSTAGRAM CAPTIONS OF @BAWABALI_OFFICIAL - Cahyani, Ni Luh Dian; Maharani, Putu Devi; Tustiawati, Ida Ayu Mela (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2022)
This study focused on identifying and analyzing the types of derivational suffixes forming noun in the Instagram caption of @bawabali_official, specifically on the posts shared from September until October 2021. The documentation method was applied in collecting the data for this study. Moreover, this study applied the qualitative-descriptive and quantitative methods in analyzing the data. The data found in this study were analyzed by adopting the theory proposed by Katamba (1994) as the main theory to answer the problem of this study. Additionally, this study also employed formal and informal methods to present the result and discussion. As the result, this study discovered 179 words containing derivational suffixes forming noun. There were 3 types of derivational suffixes forming noun discovered from the data source: 143 data (79,9%) of derivational suffixes deriving verb to noun (-age, -al, -ance, -ence, -ation, -ion, -ee, -er, -or, -ing, -ment, and -y), 26 data (14,5%) of adjective to noun (-dom, -ence, -ery, -ial, -ity, -ness, and -ship), and 10 data (5,6%) of noun to noun (-aire, -er, -ery, -ism, -ist, -ship and -y). Eventually, this study discovered that the most prominent type from these 3 types found from the data source was the derivational suffixes deriving verb to noun, which were found in 143 words (79,9%). Keywords: derivation process, derivational suffixes, Instagram caption, morphology, noun